OCCUPATIONAL STRESS AND MENTAL HEALTH IN THE POPULATION OF POLICE OFFICERS: META-ANALYTIC STUDY - Veljković, Bojan (Primenjena psihologija, 2017)
The aim of the present meta-analytic study was to quantitatively integrate findings from single studies investigating correlations between occupational stress and mental health within population of police officers. Included studies are quantitative correlational studies, published in English. Acceptable scientific sources were studies published in journals (excluding review papers) for the last 15 years. This meta-analysis included 10 papers with 10 studies and 4180 examinees from the population of police officers. Random-effects meta-analysis model was used. Average effect size, expressed by Pearson correlation coefficient, was .37 and it can be interpreted as moderate. Moderator effects of time when a study was published and the impact factor of the journal where a study was published were obtained, except that there was no significant interaction of these two moderators. The obtained average effect size should be considered as preliminary, due to certain study limitations.